SUCCESSFUL HEART TRANSPLANTATION IN PATIENT WITH CRITICAL MULTIORGAN FAILURE - L. A. Bockeria; K. V. Shatalov; N. N. Koloskova; M. B. Yarustovskii; G. V. Lobacheva; M. V. Abramian; V. Yu. Merzliakov; M. M. Rybka; S. L. Gordeev; Yu. A. Nekhai; A. A. Starovoitov; E. A. Trofimova; et al. (Сеченовский вестник, 2010)
Case of successful heart transplantation in patient with dilated cardiomyopathy, which lead to dramatic improvement of his clinical status and physical exercise tolerance, is described